Competitive Anxiety and Mood States in High-Performance Cuban Student Athletes - Jesús Ríos-Garit; Marta Cañizares-Hernández; Mario Reyes-Bossio; Yanet Pérez-Surita; Raul Touset-Riverí (Psychology in Russia: State of Art)
Background. The study of competitive anxiety and its relationship with mood states in high-performance athletes is relevant for predicting performance and enabling timely interventions to ensure successful outcomes in competitions. Due to the complex psychological demands arising from dual careers, the study of competitive anxiety and mood states contributes valuable insights into the emotional well-being of these student athletes. Objective. To examine and describe competitive anxiety and mood states in a sample of high-performance Cuban university athletes across different sports and genders. Design. A descriptive, correlational, and cross-sectional study was conducted involving 46 Cuban student athletes from national teams across 16 sports and included both male and female athletes, with an average chronological age of 20.70 years and 6.98 years of experience in a high-performance sport. The Competitive Sport Anxiety Inventory and Brunel Mood Scale were administered in their Spanish versions. The data were examined using descriptive statistics analysis including the Mann-Whitney U test, and Spearman's correlation coefficient. Results. Although no statistically significant differences were found in competitive anxiety and mood states in relation to gender and type of sport, female athletes tend to present higher mean scores in competitive anxiety and negative mood states. Additionally, female athletes in team sports experienced slightly more intense emotions. Anxiety shows positive correlations with tension, depression, and vigour, suggesting its influence on certain mood states. Conclusion. The results indicate that, in general, the intensity of certain moods in Cuban university student athletes is influenced by levels of competitive anxiety. An increase in anxiety during competition can lead to heightened tension, depression, and vigour, with no significant differences observed between female and male athletes or based on the type of sport practiced.